Skala Prioritas Kerusakan Jalan Trans Madura dengan Menggunakan Metode Analytical Hierarchy Process - Ibnu Sholichin; Masliyah Masliyah (KERN, 2020)
The existence of the Suramadu bridge and increasing regional awareness of the importance of new tourism in Madura further increases the flow of transportation in Madura. Suramadu Bridge, which is now a non-toll road, also increases property values ​​in Madura, especially the city of Bangkalan. With the increasing flow of motorized vehicles, both large and small, causing road damage along the Trans Madura road. In this study, the Analytical Hierarchy Process (AHP) method is used to determine the priority scale that causes road damage. From the results of the study, it was found that the biggest cause of road damage was the traffic factor with a value of 40.23%, with sub-criteria causing road damage was 23%. The types of damage that occur are potholes and rutting. Suggestions for improvement in the form of patching at the points of road damage. For deep enough holes, repairs also include repairing the foundation to avoid repetitive damage.